Innovative e-book to numeracy skill improvement: The role of flip HTML5 in digital pocket book development - Kadarisma, Gida; Indah, Jihan Purnama; Annisa, Delsyfa Putri; Fitria, Nury Ainun; R, Windriani (Journal of Honai Math, 2024)
This research was prompted by the observed deficiency in numeracy skills among junior high school students. Consequently, the study aims to develop digital teaching materials utilizing Flip HTML 5 to enhance these skills. The research method employed is research and development (R&D) using the 4D model: Define, Design, Develop, and Disseminate. The instruments used in this study include expert validity sheets, student response questionnaires regarding the practicality of the teaching materials, and numeracy test instruments focused on number pattern material. The limited trial involved 8 randomly selected students from a junior high school in West Bandung Regency, while the implementation stage included 26 randomly selected students from the same region. The results indicated that the Flip HTML 5-assisted digital pocketbook teaching materials developed were valid, practical, and effective in improving students' numeracy skills. This study implies that the developed teaching materials can be an alternative for teachers seeking ICT-assisted resources to enhance students' numeracy abilities.